2018
DOI: 10.5194/acp-2018-305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large simulated radiative effects of smoke in the south-east Atlantic

Abstract: Abstract. A 1200 km-square area of the tropical south Atlantic Ocean near Ascension Island is studied with the HadGEM climate model at convection-permitting and global resolutions for a ten-day case study period in August 2016. During the simulation period, a plume of biomass burning smoke from Africa moves into the area and mixes into the clouds. We examine the interaction of the smoke with clouds and find it has substantial instantaneous direct, indirect and semi-direct radiative effects, which vary in magni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 69 publications
3
4
0
Order By: Relevance
“…Such values of SW heating due to smoke appear to fall well within the range of values reported by Tummon et al (2010), Gordon et al (2018), Adebiyi et al, (2015) or Wilcox et al (2010), who reported, respectively, additional SW heating due to smoke of 1 (JJAS period), 0.34 (5 days of simulations), 1.2 (for fine AOD > 0.2) and 1.5 °K by day. In addition, Keil and Haywood (2003) estimated a SW heating rate of 1.8°K/day near the coast using a radiative transfer model and observations during SAFARI-2000.…”
Section: Sw Heating Ratesupporting
confidence: 87%
“…Such values of SW heating due to smoke appear to fall well within the range of values reported by Tummon et al (2010), Gordon et al (2018), Adebiyi et al, (2015) or Wilcox et al (2010), who reported, respectively, additional SW heating due to smoke of 1 (JJAS period), 0.34 (5 days of simulations), 1.2 (for fine AOD > 0.2) and 1.5 °K by day. In addition, Keil and Haywood (2003) estimated a SW heating rate of 1.8°K/day near the coast using a radiative transfer model and observations during SAFARI-2000.…”
Section: Sw Heating Ratesupporting
confidence: 87%
“…We are thus making an assumption that the CALIOP extinction profile is suitable for redistributing the aerosol mass profile. This is not strictly correct, as the relative humidity within the free troposphere is generally less than in the MBL, but over SE Atlantic in particular it is frequently high enough (Adebiyi et al, ; Gordon et al, ) that the hygroscopic growth can be similar to what would be experienced in the MBL. Overall, we think the assumption being made is reasonable, but we acknowledge that the mass redistribution does result in an overall decrease in the total column extinction by about 15% near the coast and a somewhat greater reduction (~30%) further west in elevated aerosol case versus the MERRAero control case.…”
Section: Approach and Methodsmentioning
confidence: 99%
“…Aerosol indirect effects might also be relevant in this region, based on the previous space‐based observational studies (Costantino & Bréon, ; Painemal et al, ) and the presence of pollution within the MBL observed in recent in situ measurements (Layered Atlantic Smoke Interactions with Clouds (LASIC), Zuidema et al, ; and ObseRvations of Aerosols above CLouds and their intEractionS (ORACLES), Diamond et al, ). In this context, regional modeling studies by Lu et al () and Gordon et al () evaluated the aerosol indirect or microphysical effects in addition to the aerosol direct and semi‐direct effects using a forecast model configuration run at a high (<5‐km grid spacing) resolution. Lu et al () found the aerosol microphysical effects play the dominant role, larger by about a factor of 2, compared to the aerosol radiative effects in determining the total radiative forcing at the TOA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations